Identification of single nucleotide polymorphisms [SNPs] at candidate genes involved in abiotic stress in two Prosopis species and hybrids - Pomponio, Maria Florencia (2014)
Aim of the study: Identify and compare SNPs on candidate genes related to abiotic stress in Prosopis chilensis, Prosopis flexuosa and interspecific hybrids Area of the study: Chaco árido, Argentina. Material and Methods: Fragments from 6 candidate genes were sequenced in 60 genotypes. DNA polymorphisms were analyzed. Main Results: The analysis revealed that the hybrids had the highest rate of polymorphism, followed by P. flexuosa and P. chilensis, the values found are comparable to other forest tree species. Research highlights: This approach will help to study genetic diversity variation on natural populations for assessing the effects of environmental changes.